(untitled) - MS.LAVANYA.V , DR.S.CHITRA (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Entrepreneurship is one area where Women Entrepreneurs can actually define a unique identity for themselves. Rural Women Entrepreneurs are recognized as a significant source of untapped economic growth. Women must now be empowered socially, economically and technologically in order to be able to stand in society. Entrepreneurship is the critical driver of any economy's innovation and growth in the current scenario. Fostering entrepreneurship is therefore the important part of many governments around the world's economic growth strategies. The research paper aims to reveal the role of government and challenges in empowering rural women entrepreneurs and their benefits. The research work is empirical in nature and primary data are collected using random sampling techniques through a structured questionnaire. The study outcome will help the business community and empower rural women entrepreneurs.